FACTORS AFFECTING THE EFFICIENCY OF FINANCIAL PERFORMANCE BASED ON BPK AUDIT RESULTS - Syarifahku Sayang; Kadir Kadir; Novita W. Respati (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
The purpose of this research is to analyze and obtain empirical evidence regarding the factors that influence the Efficiency of Financial Performance based on the results of BPK audits. BPK Audit Results consist of Audit Opinion, Audit Findings, Follow-Up of Audit Results, and Timely Submission of Regional Government Financial Reports. The data used in this study is secondary data obtained from the inspection report. The population in this study were all provinces in Indonesia during the 2016-2018 research period. Based on existing criteria, the number of samples used is 23 provinces. The data were tested using multiple linear regression. The results of the study show that only follow-up audit results have a positive effect on the efficiency of financial performance. This indicates that the government which can follow up on findings in the previous period will have efficient financial performance in the future. Meanwhile, audit opinion, audit findings and timely submission of LKPD do not influence the efficiency of financial performance.